Analysis and evaluation of the operational characteristics of a new photodynamic therapy device - Navarrete-de-Gálvez, Enrique; Aguilera-Arjona, José; Fonda Pascual, Pablo; De-Gálvez-Aranda, María Victoria; Andrés-Díaz, José Ramón; Vidal Asensi, Santiago; Herrera-Acosta, Enrique; Gago-Calderón, Alfonso (Elsevier, 2022)
One of the key aspects of photodynamic therapy is the light source that is used to irradiate the lesion to be treated. The devices used must ensure that their emission spectrum matches the absorption spectrum of the photosensitizer, so that treatment radiation is delivered only on the target area, without irradiating healthy tissue at superficial or deep levels. Irradiance values must be adequate in order to avoid thermal damage, exceed the oxygen replenishment rate and avoid long treatment times. Furthermore, the device should be user-friendly, inexpensive, and able to be adapted to different photosensitizers. We have developed an easy-to-use and highly customizable device based on LED technology. Its innovative geometric design allows radiation to be delivered to a small treatment surface, since the LEDs are arranged in three arms, the configuration of which directs their radiation on the treatment point. Different high-power color LEDs are disposed on the arms, and can be independently selected based on the most effective wavelengths for exciting the different photodynamic therapy photosensitizers. We have tested the prototype in 5 different patients (1 actinic keratose, 1 actinic cheilitis, 1 superficial basal cell carcinoma and 2 Bowen's disease) and after 1-2 sessions of total cumulative dose of 25-50 J / cm2, 100% clearance of lesions were obtained. Our device can be used by any professional in the field, whether for medical or research purposes. It facilitates the development of treatment protocols and trials with different photosensitizers.
Keywords: Espectros de absorción; Espectroscopía molecular; Fotoquimioterapia; Absorption spectrum; Emission spectrum; LED device; LED technology; Photodynamic therapy (PDT); Photosensitizer